Different socioeconomic backgrounds between hazardous drinking and heavy episodic drinking: Prevalence by sociodemographic factors in a Japanese general sample. (1st December 2018) - Kinjo, Aya; Kuwabara, Yuki; Minobe, Ruriko; Maezato, Hitoshi; Kimura, Mitsuru; Higuchi, Susumu; Matsumoto, Hiroshi; Yuzuriha, Takefumi; Horie, Yoshinori; Kanda, Hideyuki; Yoshimoto, Hisashi; Osaki, Yoneatsu
Graphical abstract: Lower educational background for both men and women was associated with a higher risk for heavy episodic drinking, while higher household income for men was associated with a higher risk for hazardous drinking in Japan. Figure Legend: OR, odds ratio; HED, heavy episodic drinking; HD, hazardous drinking. Drinkers who had neither HED nor HD were adopted as the reference group in order to calculate the OR. Highlights: The risk for hazardous drinking (HD) was higher in persons of less education for both genders. Unlike most countries, women with lower education showed higher risk of HD in Japan. Heavy Episodic Drinking (HED) risk was high among men with higher SES and among working women in Japan. HED and HD may vary with SES characteristics in the Japanese population. Abstract: Background: Hazardous drinking (HD) and heavy episodic drinking (HED) constitute different types of alcohol-related harm. The socioeconomic status (SES) background of various alcohol consumption behaviors is not clear. The purpose of this study was to clarify existing SES differences between HD and HED. Methods: The 2013 national survey regarding alcohol use among Japanese adults was utilized. The results from 1193 men and 1503 women aged 20–64 years were included in the analysis. Education attainment, household income, marital status, working status, and occupation were adopted as SES determinants. Binomial logistic regression analysis was conducted to estimate the odds ratios (ORs) of HD and HED for each SES group. Results: ORs (95% confidence intervals) of HD were higher among persons with less education among both men [1.61 (1.18–2.20)] and women [1.78 (1.19–2.67)]. The OR of HED in men was significantly higher among those who belonged to high household income, were married, and managers or professionals. The OR of HED among women was higher in persons who were employed, as compared with those who engaged in housework. There were no correlations between HED and educational background. Conclusions: This study showed that in Japan, a lower educational background for both men and women was associated with a higher risk for HD, while higher current SES for men and working women were associated with a higher risk for HED. It is necessary to recognize the SES differences between HD and HED to achieve a policy to reduce alcohol-related harm.